2019
DOI: 10.5004/dwt.2019.24241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drinking water quality using the water quality index (WQI), the synthetic pollution index (SPI) and geospatial tools in Thatta district, Pakistan

Abstract: The objective of the present study was to evaluate the quality of groundwater in the deltaic region of the Indus River in district Thatta, Pakistan. In the region, the groundwater is widely used for drinking purposes. Due to excessive abstraction rates of groundwater, a significant amount of seawater intrudes into the aquifers. The situation is, furthermore aggravated by dwindling flows of freshwater from the river Indus. Thus, groundwater samples (100) were analyzed for different physicochemical parameters. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…Among all the parameters, the average concentration of DO (7.3 mg/L), nitrate (3.2 mg/L), and phosphate (1.3 mg/L), as shown in Tables 4-6, were within standard limits [22,23]. These findings were similar to the available studies [11,40,41]. However, few samples exceed the standard limit for phosphate and nitrogen.…”
Section: Dissolved Oxygen (Do) Nitrate and Phosphatesupporting
confidence: 86%
See 2 more Smart Citations
“…Among all the parameters, the average concentration of DO (7.3 mg/L), nitrate (3.2 mg/L), and phosphate (1.3 mg/L), as shown in Tables 4-6, were within standard limits [22,23]. These findings were similar to the available studies [11,40,41]. However, few samples exceed the standard limit for phosphate and nitrogen.…”
Section: Dissolved Oxygen (Do) Nitrate and Phosphatesupporting
confidence: 86%
“…The high average TDS level was between 1000-1250 mg/L, which exceeded WHO recommended limits in South Sindh [23], and, overall, TDS exceeded the limits in 33% of the samples. Regionally, TDS was elevated in 36% of the samples from South Sindh when compared North Sindh (29%) and Central Sindh (33%), as shown in previous studies [7,40,41], which took samples from community water sources rather than schools, showed variation in TDS results by location and water source (ground and surface) which is consistent with our findings, and we can expect larger TDS with surface water [7,40,41]. A few studies in the same study population (community settings) found different results, which could be due to water treatment, the difference in study methods (small sample size, sampling technique, non-representative sample, etc.…”
Section: Total Dissolved Solids (Tds)supporting
confidence: 79%
See 1 more Smart Citation
“…5, among the 71 groundwater samples, 45 were "excellent" (grade 1), 20 were "good" (grade 2), 4 was "poor" (grade 3), and 2 were "very poor" (grade 4), accounting for 63.38%, 28.16%, 5.63%, and 3.63%, respectively. The calculation results of WQI show that the groundwater in the study area is excellent for drinking purpose, while the groundwater in some places is not suitable for drinking [39][40][41].…”
Section: Water Quality For Drinking Purposementioning
confidence: 99%
“…Most of its area stretches in two district administrative boundaries of Sindh Province, Pakistan, i.e., Thatta, and Sujawal ( Figure 1). The area hardly receives about 220 mm of rainfall annually [14][15][16][17][18], mostly falls during monsoon periods. According to the 2017 Census, about 1.76 million people are living in these two districts.…”
Section: Study Areamentioning
confidence: 99%